Breaking the Silence: An innovative ASL to Text Conversion System Leveraging Computer Vision & Machine Learning for Enhanced Communication - Bagane, Pooja; Thawani, Muskaan; Singh, Prerna; Ahmad, Raasha; Mital, Rewaa; Jebessa, Obsa Amenu (International Journal of Intelligent Systems and Applications in Engineering, 2024)
An innovative approach for converting American Sign Language (ASL) into text is proposed in this paper. The technology accurately recognises and instantly translates ASL signals into written text using cutting-edge computer vision and machine learning algorithms. A letter recognition model, a gesture recognition module, and a text generating module make up the suggested system. Then, using the recognised movements, the text production module produces text. The proposed technology may enhance hearing and deaf people’s ability to communicate. To help deaf and mute people communicate with other people more successfully, the system can be used to translate ASL into text. Our study describes how ASL to text converters might be used in accessibility services, education, and ordinary communication.